2005
DOI: 10.3758/bf03195341
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-handed advantage in episodic memory: A possible role of interhemispheric interaction

Abstract: and KERI ANN PHANEUF Merrimack College, North Andover, MassachusettsRecent behavioral and brain imaging data indicate that performance on explicit tests of episodic memory is associated with interaction between the left and right cerebral hemispheres, in contrast with the unihemispheric basis for implicit tests of memory. In the present work, individual differences in strength of personal handedness were used as markers for differences in hemispheric communication, with mixed-handers inferred to have increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
105
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 44 publications
6
105
0
3
Order By: Relevance
“…For continuity, we compared nSR and SR subjects in our no-movement condition. Replicating Propper et al (2005), we found that nSR subjects recalled more studied words (M 14.2) and fewer extralist intrusions (M .31) than did SR subjects (Ms 12.4 and .93, respectively). The difference was significant for false recall [t(68) 2.72, p .008], but not correct recall [t(68) 1.23, p .22] (see Christman et al, 2004, for a similar pattern).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…For continuity, we compared nSR and SR subjects in our no-movement condition. Replicating Propper et al (2005), we found that nSR subjects recalled more studied words (M 14.2) and fewer extralist intrusions (M .31) than did SR subjects (Ms 12.4 and .93, respectively). The difference was significant for false recall [t(68) 2.72, p .008], but not correct recall [t(68) 1.23, p .22] (see Christman et al, 2004, for a similar pattern).…”
Section: Resultsmentioning
confidence: 60%
“…The interaction of handedness and pretest activity was significant [F(1,135) 9.35, p .003, p 2 .07], and is apparent in Figure 2. For SR subjects, eye movements (M .51) produced significantly lower false recall than did no movement (M .93) [t(83) 2.01, p .048], but the reverse effect occurred for nSR subjects, whose false recall was significantly greater following eye movements (M Cabe, & Roediger, in press;Propper, Christman, & Phaneuf, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that inconsistent-handers have superior episodic retrieval of both lab-based (Chu, Abeare, & Bondy, 2012;Lyle, Hanaver-Torrez, Hackländer, & Edlin, 2012) and real-world memories (Propper, Christman, & Phaneuf, 2005), as well as better source memory (Lyle, McCabe, & Roediger, 2008;Parker & Dagnall, 2010), fewer false memories (Christman, Propper, & Dion, 2004), a greater proportion of Bremember^relative to Bknow^responses in recognition memory , an earlier offset of childhood amnesia (Christman, Propper, & Brown, 2006), better memory for prior hand usage (Edlin, Carris, & Lyle, 2013), better learning of foreign vocabulary (Kempe, Brooks, & Christman, 2009), and better incidental learning (Alipour, Aerab-Sheybani, & Akhondy, 2012;Christman & Butler, 2011).…”
mentioning
confidence: 99%
“…The relationship between handedness and awareness with recall has yet to be investigated; however, neuropsychological research suggests a potential link between handedness and memory. For example, studies have demonstrated weaker performance in right-handers on tests of episodic memory, a form of explicit memory that requires inter-hemispheric communication [12][13][14]. Consistent right-handers, i.e.…”
Section: Introductionmentioning
confidence: 99%